MANAGEMENT OF THE EQUIPMENT AND INSTRUMENTS INVOLVED IN THE TECHNOLOGY OF FLEXIBLE REMOVABLE PROSTHESES - Ștefan Lucian Burlea; Razvan Constantin Anghel; G.Gabriel Condurache; Elena Mihaela Carausu (Romanian Society of Oral Rehabilitation, 2021)
The treatment with partially removable prostheses has become more and more complex over time, especially in the last few decades. And when it is planned correctly, and executed responsibly, it will actually help preserve the remaining dental units. Consequently, performing the treatment in a defective manner, can trigger the resorption of the bone support and can accelerate the degradation of the remaining units, resulting in their loss.Elastic prostheses are the most modern alternative to injectable acrylic prostheses. The material is elastic, with a thinner thickness than conventional prostheses, resistant to pressure and dynamic movements during chewing, and very well approved from a biocompatible point of view by the tissues of the oral cavity. The reasons for choosing to treat partial edentulousness with partially removable elastic prosthesis are the feasibility and reliability of this.